On becoming ready to pursue a goal you don't know you have: Effects of nonconscious goals on evaluative readiness - Ferguson, Melissa J. (2008)
Findings showed that the nonconscious activation of a goal in memory led to increased positive implicit attitudes toward stimuli that could facilitate the goal. This evaluative readiness to pursue the nonconscious goal emerged even when participants were consciously unaware of the goal-relevant stimuli themselves. The effect emerged the most strongly for those with some skill at the goal, and for those for whom the goal was most currently important. The effect of implicit goal activation on implicit attitudes emerged in both an immediate condition as well as a delay condition, suggesting that a goal rather than a non-motivational construct was activated. Participants' implicit attitudes toward a nonconscious goal also predicted their goal-relevant behavior. These findings suggest that people can become evaluatively ready to pursue a goal whenever it has been activated -- a readiness that apparently does not require conscious awareness or deliberation about either the goal or the goal-relevant stimuli. Theoretical implications of this type of implicit goal readiness are discussed.